MIND/BODY/SPIRIT COMPLEX IN QUANTUM MECHANICS. - Riddle, Justin M. (Cosmos & History, 2014)
Prevailing theories of consciousness may be characterized as either a physicalist view of mind with material building blocks that grow in complexity unto an emergent conscious experience, or as a dualistic model in which mind-body interaction is taken as the interface of conscious intent and unconscious bodily processing. Roger Penrose supports a model of consciousness that goes beyond dualism by adding a third domain [19]. The Three World model describes interconnected yet independent aspects of consciousness: Physical, Mental & Platonic. These three worlds are grounded in the three axioms of quantum mechanics: measurement, superposition and entanglement. The Mental World corresponds to the superposition principle in which all possible future realities are superposed as potentials before a choice is made. The superposition is analogous to the choices we make everyday. In the Physical World, the measurement principles states that the quantum system must collapse the superposed possibilities into a single actuality. The most peculiar phenomenon in quantum mechanics is entanglement. Quantum systems may be entangled in a timeless and spaceless way such that they will still be connected despite separation in space or time. The Platonic World is akin to entanglement, because mathematics and conceptual forms are unchanging regardless of space or time. Finally, a new model called Fractal Trialism is proposed which describes how there is a nested trialism within each of the three worlds in order to elaborate their interconnectedness. This model describes digital computers, quantum computers and shared experience.